Development of IIUM Free Wing Unmanned Aerial Vehicle (IIUM-FWUAV) - Omar, Ashraf Ali; Kurban, Adel; Baharuddin, Khairun Nisaa; Ibrahim, Idasary (2010)
This research focused on the design, construction and testing of a free wing remote controlled aerial vehicle. The free wing concept allows the wing to move freely in pitch relative to the fuselage. Its main advantage is stall avoidance which is achieved through the natural property of the airfoil. In constructing the aerial vehicle, the initial weight is estimated and the wing size, fuselage size and aerodynamic forces prediction are determined. Optimization of the aircraft is done through trial and error method. The developed free wing unmanned aerial vehicle (FW-UAV) flew successively. In this study, the free wing has been proven to be a very efficient unmanned aerial vehicle.